KEEFEKTIFAN MEDIA AUDIO VISUAL YOUTUBE MISS IMAS DALAM PEMBELAJARAN MENULIS TEKS NARASI PADA SISWA KELAS VII FASE D - Dianti, Dea; Soedarto Harjono, Hary; Oktri Wini, Lusia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of Miss Imas YouTube audio-visual media on the writing skills of seventh-grade students (Phase D) at SMP Negeri 2 Kota Sungai Penuh. The background of this research is predicated on students' low writing proficiency, attributed to a lack of variety in instructional methods and the minimal use of technology-based learning media. This study employed a quantitative approach with a Quasi-Experimental method (Nonequivalent Control Group Design). The research sample consisted of Class VII B (control group) with 27 students and Class VII D (experimental group) with 27 students, selected using a cluster sampling technique. Data collection was conducted through observation, testing, and documentation. The data were analyzed using descriptive statistical analysis, normality tests, homogeneity tests, and hypothesis testing (t-test) facilitated by Microsoft Excel 365 and IBM SPSS Statistics version 25. The results indicated that the average score of the control group increased from 53.76 in the pre-test to 61.85 in the post-test. Meanwhile, the experimental group’s average score rose significantly from 49.50 in the pre-test to 73.45 in the post-test. Based on the Independent Sample T-test, a significance value of 0.003 (p < 0.05) was obtained, indicating a significant difference in post-test scores between the control and experimental groups. Consequently, it can be concluded that the use of audio-visual media is significantly effective in enhancing students' writing skills. This research implies that Indonesian language teachers can utilize audio-visual media as an effective, innovative, and engaging instructional tool to improve students' writing abilities.